ANALISIS DAMPAK TANGGUL TERHADAP ELEVASI BANJIR SUNGAI NAGARA KALIMANTAN SELATAN - Dyah Indriana Kusumastuti (UNIVERSITAS LAMPUNG, 2011)
Nagara River is a river in South Kalimantan province with extensive swamp area which formsseasonal flood plain and protects downstream area from flooding and salt water intrusion. Theplan for land use change from the swamp area to plantation area involves building dyke on thesides of Nagara River. This research aims to analyze the elevation of Nagara River duringflooding when the swamp area is occupied as an extension of flood plain, compared that resultedfrom the scenario when this area is converted into plantation area which needs dyke on the sidesof the river for flood protection. There are two kinds of scenarios, first only one side of the riverwhich will be build dyke, and second both sides of the river will be built dykes. The analysisinvolved rainfall data analysis using daily module rainfall, design discharge analysis usingRational Method and hydraulic analysis using HEC-RAS software with one-dimensional steadyflow. The result shows that using dyke at elevation +11.00 m, the increase of water level is notsignificant while one side of the river is protected by dyke. An increase of 30 cm of water elevationis obtained using scenario of both sides are protected by dykes. The increase of water level maycause flooding in the area located at the upstream and downstream of the plantation area.